THE EFFECTIVENESS OF MOBILE APPLICATION LEARNING MEDIA IN SUPPORTING BLENDED LEARNING AT STATE ELEMENTARY SCHOOL 1 BANYUATES - Suhendro, Dodiek; Sucipto, Sucipto; Tobing, Victor Maruli Tua L (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to analyze the effectiveness of mobile app-based learning media in supporting blended learning implementation at SMPN 1 Banyuates. The research employed a quasi-experimental design with a pretest-posttest model and control group. The research subjects were 62 eighth-grade students divided into an experimental group (n=32) and a control group (n=30). The experimental group used interactive mobile apps integrated with face-to-face learning, while the control group followed conventional learning. Data were collected through learning achievement tests, student engagement observation sheets, and perception questionnaires. Results showed that the experimental group experienced an average score improvement of 11.63 points compared to 5.47 points in the control group. Independent t-test yielded p-value = 0.008 (p < 0.05) with Cohen’s d = 0.52, indicating a statistically significant moderate effect. These findings suggest that mobile app usage in blended learning effectively improves student learning outcomes, although there remains room for further optimization.